The People's Health - Hastings, Somerville, 1878-1967 (London : The Labour Party)
1932-07 1932 1930s 24 pages another:— cash benefit and medical benefit, by which latter is described the limited treatment provided by the National Health Insurance Act. Now there is a good deal to be said for the retention of the administration of cash benefit by the Approved Societies, but the treatment of sickness in the insured being a matter of national as well as personal importance, is much better in the hands of an authority that is dealing with other medical problems and has to consider questions of prevention as well as cure. Accordingly one of the first steps must be the transference from the Insurance Committees to the Local Health Authorities of the administration of medical benefit together with those funds (contributed by the employers, the employed, and the State) which are now earmarked for providing medical benefit. To ensure that the experience gained by the present members of the Insurance Committees may not be lost, it may be wise to allow co-option to the extent of one-third by the sub-committees of the Public Health Committees, which will necessarily be formed for the adminstration [administration] of medical benefit. The next step will probably be the provision as a right of consultant services and dental benefit to all insured persons. In connection with the latter it would be found most convenient to carry out the dental work in clinics served by full-time dentists under the control of the Local Health Authorities. These clinics might be situated in the municipal buildings or elsewhere and they could be used also for the dental treatment of patients from the Maternity and Child Welfare Centres and for the dental inspection and treatment of school children, and no doubt the same dental personnel would be able to carry out each and all of these separate duties. In the same way the consultants, who would consult with the panel practitioners, either in the patients' home, when necessary, or elsewhere, would be in most cases the same individuals who gave specialist advice in connection with the Poor Law Medical Service, the Municipal Hospitals and the School Medical Service, and wherever the amount of work justifies this course, these officers would be full-time. Administratively, it will be an easy matter to extend the panel service organised as above, together with the consultant and dental services, to the dependents of the insured. Admittedly this will be a somewhat costly matter, but it does not necessarily follow that the scale of remuneration of the personnel involved will be necessarily what it is at the moment. It is possible that there might be a tendency on the part of members of the extended panel service to exploit to their own advantage, this sudden increase in the number of insured patients. As at present, the number of panel patients allotted to each practitioner 16 292C/155/1/1